Community-aquired pneumonia on the background of coronaviral disease (COVID-19): principles of diagnostics and determination of risk factors of pathological process aggravation - Pertseva, T. A.; Bielosludtseva, K. O.; Kirieieva, T. V.; Konopkina, L. I.; Krykhtina, M. A.; Basina, B. A.; Matykina, N. N.; Turchin, N. A. (Medicni Perspektivi, 2020)
The diagnosis of community-acquired pneumonia (CAP) on the background of COVID-19 is especially actual due to the prevalence of this pathology and the possible aggravation of the pathological process. The aim of our study was to improve the principles of CAP diagnostics on the background of COVID-19 and to determine risk factors for aggravating of the pathological process. Patients with respiratory symptoms who were hospitalized with suspected COVID-19 were examined. General clinical research methods were carried out, determination of SARS-CoV-2 virus RNA by PCR method, computer tomography (CT) to identify the features of lung tissue damage was performed. The main observation group consisted of 37 patients (men – 19 (51.4%), average age – 61 (57; 69) years) with pneumonia on the background of confirmed COVID-19. According to the severity of coronavirus disease, all patients of the main group were divided into 3 subgroups: subgroup 1 included 17 people with moderate COVID-19, subgroup 2 – 13 people with severe COVID-19, subgroup 3 – 7 people with critical COVID- 19 course. The levels of markers of systemic inflammation (C-reactive protein (C-RP) and fibrinogen) were also determined. Since patients with COVID-19 of moderate severity (which is characterized by the presence of community-acquired viral pneumonia) belong to the risk group of severe and critical course, it is suggested to consider the following risk factors for aggravating the pathological process as: temperature over 38.5°C, heart rate over 90 per minute, respiratory rate over 20 per minute, SpO2 ≤ 93%; absolute lymphopenia (less than 0.9 G/L) and an increase in serum levels of C-RP more than 50 mg/L and fibrinogen more than 5 g/L.